Analisis Pengelolaan Keuangan Puskesmas Buniwangi Dalam Upaya Meningkatkan Efisiensi Dan Efektivitas Penggunaan Anggaran - Siti Rahmah Rohilah; Tina Kartini; Andri Indrawan (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2025)
This research aims to analyze financial management at the Buniwangi Community Health Center in order to increase the efficiency and effectiveness of budget use. Good financial management is a key factor in ensuring optimal allocation and use of financial resources, especially in the health service sector which has a major responsibility for community welfare. This research uses a qualitative approach with descriptive methods, involving in-depth interviews, document analysis, and observation as the main data collection techniques. The results of the research show that financial management at the Buniwangi Community Health Center has met most public financial management standards, but there are still several obstacles that affect the efficiency and effectiveness of budget use, such as a lack of staff understanding of accounting procedures, limited supporting technology, and budget allocations that are not in accordance with priority needs.